Joint-Preserving Surgery for Hyperextension Deformity of the Hallux Interphalangeal Joint in a Patient with Rheumatoid Arthritis - Matsumoto, Takumi (Case Rep Orthop, 2020)
Interphalangeal hyperextension is one of the major hallux deformities in patients with rheumatoid arthritis; however, there is yet no established surgical method for this deformity. We here present the case of a 69-year-old female patient with rheumatoid arthritis who developed hallux interphalangeal hyperextension and painful callosity on the plantar hallux accompanied by limited dorsiflexion at the metatarsophalangeal joint. Lateral weight-bearing radiograph of the foot revealed misalignment of the medial column and hallux, including a collapsed medial arch, elevated first metatarsal, plantar flexion and deviation of the proximal phalanx, and hyperextension of the distal phalanx. The foot was successfully treated and became symptom-free with opening wedge osteotomy of the medial cuneiform, plantar and proximal translation of the metatarsal head, and tenotomy of the extensor hallucis longus. This case suggests that reconstruction of the sagittal alignment of the medial column and hallux through a combination of osteotomy and soft tissue intervention could be an optional treatment for interphalangeal hyperextension.